Improvement of the constitutional mechanism for the protection of constitutionalism in Russia - V. A. Simonov (Правоприменение)
The subject. The article names the conflict situations that have developed in the Russian Federation that threaten Russian constitutionalism, searches for ways to resolve them, and outlines measures to improve the constitutional and legal protection of the constitutional system and the territorial integrity of our state.The purpose of this article is to identify threats to constitutionalism in the Russian Federation from the point of view of the ethnopolitical and historical development of Russia as well as to identify conflict situations that generate these threats.The methodology. Dialectical method, systematic approach and system analysis, formaldogmatic, logical-legal, comparative-legal, concrete-historical and sociological methods were used.The main results, scope of application. The article indicates the impact on Russia of the negative processes that led to mass riots in foreign countries, and the conflict situations caused by them. When destabilizing public relations in Russia, one of the first places is occupied by inciting hostility on the basis of national relations, first of all, inciting an aggressive minority against a state-forming ethnic group. Grievances and disagreements that took place in the historical past, as well as contradictions of an interfaith and intercultural nature are used as reasons.The article makes proposals for the prevention, suppression and elimination of negative processes and conflict situations aimed at strengthening Russian constitutionalism.They are reduced not only to strict compliance with the existing constitutional and sectoral norms; elimination of contradictions in the Constitution, as well as the specification of constitutional norms by sectoral rules; timeliness, proportionality and inevitability of state coercion measures applied to offenders. Restoration and accelerated development of sectorsof the national economy destroyed during the perestroika; increasing the number of jobs with decent wages; employment of citizens of the Russian Federation first of all; comprehensive expansion of the network of professional training in industrial and technical specialties are among the important measures to protect constitutionalism.